Total Synthesis of the 7, 10‐Epimer of the Proposed Structure of Amphidinolide N, Part II: Synthesis of C17–C29 Subunit and Completion of the Synthesis. Issue 10 (4th February 2016) - Ochiai, Koji; Kuppusamy, Sankar; Yasui, Yusuke; Harada, Kenji; Gupta, Nishant R.; Takahashi, Yohei; Kubota, Takaaki; Kobayashi, Jun'ichi; Hayashi, Yujiro
Abstract: The total synthesis of 7, 10‐epimer of the proposed structure of amphidinolide N was accomplished. The requisite chiral C17–C29 subunit was assembled stereoselectively via Keck allylation, Shi epoxidation, diastereoselective 1, 3‐reduction, and a later oxidative synthesis of the THF framework. The C1–C13 and C17–C29 subunits were successfully coupled using a Enders RAMP "linchpin" as the C14–C16 three carbon unit, thereby controlling the chirality at C14 and C16. The labile allyl epoxy moiety was successfully constructed by Grieco–Nishizawa olefination at a final stage of the synthesis. Abstract : RAMP linchpin : The total synthesis of the 7, 10‐epimer of the proposed structure of amphidinolide N is described (see scheme). The requisite chiral C17–C29 subunit was assembled stereoselectively via Keck allylation, Shi epoxidation, diastereoselective 1, 3‐reduction, and a later oxidative synthesis of the THF framework. The C1–C13 and C17–C29 subunits were successfully coupled using an Enders RAMP "linchpin" as the C14–C16 three carbon unit, thereby controlling the chirality at C14 and C16.